Milton Keynes: an outline cost-benefit study - Lennox, S. G.; Tidbury, Joan (College of Aeronautics, 1968)
This is a preliminary survey of some of the factors which would need to be investigated in the design and cost-benefit analysis of alternative transport systems for Milton Keynes. It outlines the framework within which further work can be developed and provides some order-of-magnitude estimates for basic elements in the transport cost-benefit equations.